In what ways and to what extent is the global oil and gas industry able to deliver enduring empowerment outcomes for women in Asia-Pacific? : a case study exploring the employment and skills development of Timorese women on Timor Sea offshore facilities : a dissertation presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Development Studies, Massey University, Palmerston North, New Zealand - Adams, Virginia (Massey University, 2020)
The sustainable development agenda seeks to enlist big business as a development agent to help redress persistent and pervasive conditions of women’s disadvantage in the developing world. Global corporations are being urged, among other imperatives and initiatives, to open decent work opportunities for females, thereby enabling them to traverse the basic empowerment thresholds of enjoying dignity of and in work and of becoming economically self-reliant. Rare to find in the development literature, this case study brings to light a corner of global industry (that of offshore oil and gas operations in the Timor Sea) in which, irrespective of sustainable development’s grand vision for women’s empowerment, opportunities have opened for host-country women to enjoy capabilities gains beyond the crossing of these thresholds. Moreover, the study, atypically to the dis-empowered portraits of women that abound in the development literature, brings to life the existence and experiences of dissident female (Timorese) identities imbued with high levels of agency who have been able to navigate the mesh of patriarchal belief structures and norms in their society and enter, earn respect and realise potential in the nontraditional, historically masculinised job field of offshore oil and gas. The case study has considerable breadth of scope in its pursuit of two main interconnected avenues of inquiry relating to the Timorese females’ work skills development and employment. These are: a) the associated agendas, workplace protocols, decision-making and ensuing actions within the stakeholder organisational networks of the Timor Sea oil and gas projects, and: b) the women’s own aspirations, efforts and achievements. The research methods used, of qualitative, open-ended interviews combined with long-term on-going communication with many of the group have provided a considerable depth of insight into the women’s empowerment trajectories, and a detailed illumination of the human and organisational influences on these within their training and work spaces. Near-40 Timorese women took part in the study along with 20 respondents from the stakeholder companies involved directly or indirectly with their oil and gas industry learning and earning journeys. What this research says helps to construct a more textured narrative around how gender and development is framed. It does this by capturing in multidimensional (personal, relational, social and economic) and multifaceted (cognitive, psychological and practical) ways the meanings of the empowerment gains of women from a male –dominated society who have trained, worked and been well-paid in gender-equal employment spaces. The conceptual lens is shaped using as a starting point Sen’s Capabilities Approach, feminist notions of power, theory on self-determination and around the meeting of employees’ cognitive, psychological and social empowerment needs in the workplace. The dissertation introduces a new methodological tool of the women’s owned ‘human capital portfolios’ (as their offshore-enhanced caches of knowledge, skills, abilities and attributes) to encapsulate the ballast of their capabilities sets as these contribute to their empowerment status. With its main aim being to evaluate not simply the achievement of but, importantly, the durability of the women’s empowered identities into uncertain futures, the knowledge produced in this research provides critical meaning around women’s empowerment often neglected in gender and development discourse.
Keywords: Women oil industry workers; Employee empowerment; Timor-Leste; Offshore oil industry; Offshore gas industry; Employees; 440499 Development studies not elsewhere classified